2011
DOI: 10.1107/s0021889811030226
|View full text |Cite
|
Sign up to set email alerts
|

Combined synchrotron X-ray and image-correlation analyses of biaxially deformed W/Cu nanocomposite thin films on Kapton

Abstract: In situ biaxial tensile tests within the elastic domain were conducted with W/Cu nanocomposite thin films deposited on a polyimide cruciform substrate using a biaxial testing machine developed on the DiffAbs beamline at the Synchrotron SOLEIL. The mechanical behaviour of the nanocomposite was characterized at the micro-and macroscales using synchrotron X-ray diffraction and digital image-correlation techniques simultaneously. Strain analyses for equibiaxial and non-equibiaxial loading paths were carried out. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 51 publications
3
22
0
Order By: Relevance
“…The experimental setup is illustrated and described elsewhere. 23,24 All in-situ tensile tests were conducted using a step by step loading procedure. The value of the applied load is given by the load cell for each loading step; the corresponding applied stress for a load of 100 N is 39 MPa based on the sample geometry.…”
Section: Mechanical Test and Strain Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental setup is illustrated and described elsewhere. 23,24 All in-situ tensile tests were conducted using a step by step loading procedure. The value of the applied load is given by the load cell for each loading step; the corresponding applied stress for a load of 100 N is 39 MPa based on the sample geometry.…”
Section: Mechanical Test and Strain Measurementsmentioning
confidence: 99%
“…23 Combined strain measurements approach has been applied using X-ray diffraction (XRD) and digital image correlation (DIC) in order to accurately characterize the early stages of the mechanical deformation of nanostructured thin films. 24 It has been shown that the deformation is transmitted unchanged through the metal film/ polyimide substrate interface even for two materials with such a high mechanical contrast and where the interface morphology plays an important role on the physical properties of coatings. 25,26 A previous study of gold thin film on Kapton substrate has also confirmed the complete strain transfer through the film-substrate interface where the elastic responses of both film and substrate have been measured using synchrotron XRD.…”
Section: Introductionmentioning
confidence: 99%
“…An integration procedure (see x3.3) was used to get a classical diffractogram from which the Bragg peak position is obtained using a fitting procedure (Pearson VII function and linear background). The lattice strain is thus measured with a very high accuracy (about 5 Â 10 À5 ) thanks to the so-called sin 2 analysis of the 17 data points (Dö lle, 1979;Djaziri et al, 2011;Hauk, 1997).…”
Section: Tablementioning
confidence: 99%
“…At the macro-scale, DIC was used to assess macroscopic applied strains in the polyimide cruciform substrate. The image of the bottom side of the substrate (the uncoated side) was captured using a CCD camera [42]. The applied loads are incrementally increased from the initial loading state.…”
Section: Strain Measurementsmentioning
confidence: 99%
“…It is noteworthy to recall each XRD point of the curve is the result of the analysis of seventeen  experimental points obtained thanks to the XPAD detector. Validation has been achieved by checking the measurement accuracy and the method reliability for the two types of analyses (synchrotron XRD and DIC) for which thin films deposited on polymer substrate have been adopted [42]. The consequence of the accuracy of the two strain measurements techniques is that the applied strain is determined to be transmitted unchanged in the elastic domain through the metallic film -polymeric substrate interface although no adhesion layer was used as already reported for gold films [53].…”
Section: Elastic Responsementioning
confidence: 99%